'If it is not in Wikipedia, blame yourself:' edit-a-thons as vehicles for computer supported collaborative learning in higher education. Issue 5 (3rd May 2020) - Lauro, Frances Di
ABSTRACT: This paper brings to light the notable contributions of Wikipedian Adrianne Wadewitz (1977–2014) who enlisted her peers and students to help reduce the gender imbalance by participating in mass collaborative initiatives like edit-a-thons to increase the stock of knowledge about and of interest to women. Such projects, and the edit-a-thons that continue to be convened in Wadewitz's honour, help to reconcile the imbalance and simultaneously present pedagogical opportunities. Drawing upon scholarly literature, this paper also illustrates how Wikipedia editing supports and reinforces the principles of both academic and public writing and represents an open and sustainable platform for formative and summative assessment. Moreover, the paper emphasises the superiority of digital informative texts created by mass-collaboration and participation over those compiled by individuals or through small group collaboration, both of which delimit the homogeneity of networked knowledge.